If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -10 = 2(3x + -20) Reorder the terms: -10 + 3x = 2(3x + -20) Reorder the terms: -10 + 3x = 2(-20 + 3x) -10 + 3x = (-20 * 2 + 3x * 2) -10 + 3x = (-40 + 6x) Solving -10 + 3x = -40 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. -10 + 3x + -6x = -40 + 6x + -6x Combine like terms: 3x + -6x = -3x -10 + -3x = -40 + 6x + -6x Combine like terms: 6x + -6x = 0 -10 + -3x = -40 + 0 -10 + -3x = -40 Add '10' to each side of the equation. -10 + 10 + -3x = -40 + 10 Combine like terms: -10 + 10 = 0 0 + -3x = -40 + 10 -3x = -40 + 10 Combine like terms: -40 + 10 = -30 -3x = -30 Divide each side by '-3'. x = 10 Simplifying x = 10
| -2a+1=9 | | 7x-98=-x+134 | | a=3y-4 | | 16-8n=-8(5n+7)+8 | | 4t+9=11t-83 | | 5x+7-2=5+x | | 2(3x+1)=2x+11 | | x-50=90+8x | | 5x+7-2=5tx | | 4n-(9-3n)=8n-1 | | 98+45=458 | | 4x+6x+40=0 | | 7ln(x+2)-8lnx= | | 3n+8(2n-6)=2+14n | | 8x+6=4x-58 | | -6x-62=-x+43 | | 50t=.25t+1000 | | -3(x-11)=12 | | -6x-62=-x+134 | | 24+18x=7x-7+1 | | 40x^2-41x+10=0 | | 16w-48+-4-20w=0 | | -24x+12x=35 | | -90+12x=130+x | | 6x-1=11+5x | | -151-10x=-x+56 | | 2x-4=x+3 | | 3x-0.5=10 | | 4(x-5)+2=-2(x-3) | | -3(2s-1)-3=-2(6s+4)-2 | | -42=b/(-4)+8 | | -90+8x=24+2x |